2013
DOI: 10.4161/nucl.27413
|View full text |Cite
|
Sign up to set email alerts
|

Label-free mass spectrometry exploits dozens of detected peptides to quantify lamins in wildtype and knockdown cells

Abstract: L abel-free quantitation and characterization of proteins by mass spectrometry (ms) is now feasible, especially for moderately expressed structural proteins such as lamins that typically yield dozens of tryptic peptides from tissue cells. using standard cell culture samples, we describe general algorithms for quantitative analysis of peptides identified in liquid chromatography tandem mass spectrometry (Lc-ms/ms). the algorithms were foundational to the discovery that the absolute stoichiometry of a-type to b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Noteworthy, the nucleoplasmic fraction of lamin A but not lamin C had increased mobility in cells with decreased amount of nucleoplasmic lamin B1 (Shimi et al 2008). Very recently, a study by Swift has shown that siRNA was able to knockdown more lamin A than lamin C (Swift et al 2013a). These findings might indicate that lamin A is less stable and more susceptible to various influences than lamin C. Another recent report by Swift et al has demonstrated increased lamin A expression during differentiation of bone (Swift et al 2013b).…”
Section: Different Regulation Of A-type Laminsmentioning
confidence: 92%
“…Noteworthy, the nucleoplasmic fraction of lamin A but not lamin C had increased mobility in cells with decreased amount of nucleoplasmic lamin B1 (Shimi et al 2008). Very recently, a study by Swift has shown that siRNA was able to knockdown more lamin A than lamin C (Swift et al 2013a). These findings might indicate that lamin A is less stable and more susceptible to various influences than lamin C. Another recent report by Swift et al has demonstrated increased lamin A expression during differentiation of bone (Swift et al 2013b).…”
Section: Different Regulation Of A-type Laminsmentioning
confidence: 92%
“…Quantification of proteins by label-free MS is described in the Supplemental Information and earlier work [34]. MS response to phosphorylation at S22 and S390 was calibrated using synthetic versions of tryptic peptides (SGAQASSTPLSPTR, SGAQASSTPL[pSer22]PTR, LRLSPSPTSQR LRL[pSer390]PSPTSQR; GenScript), which were spiked into a tryptic cell digests (60 – 80 kDa MW band) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1B, left panel). By using quantitative label-free mass spectrometry for proteomic profiling (Swift et al, 2013a), we have shown that collagens and other ECM-associated proteins scale with tissue elasticity (Swift et al, 2013b). Mass spectrometry was also used to quantify ,100 of the most abundant proteins in the cytoskeleton and nucleus, and we found that the elasticity of bulk tissue is strongly correlated with the composition of the nuclear lamina in terms of its content of Atype and B-type lamins (Fig.…”
Section: Scaling Of Ecm and Lamina Components In Mature And Developinmentioning
confidence: 99%